2014
DOI: 10.1002/cam4.228
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of HER2 expression between primary colorectal cancer and their corresponding metastases

Abstract: The aim of this study was to compare human epidermal growth factor 2 (HER2) status in primary colorectal cancer and paired liver or lung metastasis. Gene amplification of HER2 has been intensively evaluated in contemporary oncology, especially in breast and stomach cancer. The knowledge of HER2 status in primary and metastatic sites may be of potential value for therapeutic decision making in metastatic colon cancer. The HER2 status was assessed by fluorescence in situ hybridization (FISH) and immunohistochemi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(50 citation statements)
references
References 24 publications
6
39
0
Order By: Relevance
“…The rate of HER2/ neu amplification was lower in our study compared to published literature but differential amplification was observed in primary colon tumors and lung metastases (1.8% vs 4%). Previous studies have quoted a 5-9% incidence of HER2/neu amplification in CRC 26,27 and HER2/neu amplification was shown to be concordant in only 5% of the primary and metastatic lesions. 27 In a study by Ramanathan et al, HER2/neu-positive patients with advanced colorectal cancer were treated with trastuzumab (Herceptin Ò and irinotecan).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The rate of HER2/ neu amplification was lower in our study compared to published literature but differential amplification was observed in primary colon tumors and lung metastases (1.8% vs 4%). Previous studies have quoted a 5-9% incidence of HER2/neu amplification in CRC 26,27 and HER2/neu amplification was shown to be concordant in only 5% of the primary and metastatic lesions. 27 In a study by Ramanathan et al, HER2/neu-positive patients with advanced colorectal cancer were treated with trastuzumab (Herceptin Ò and irinotecan).…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have quoted a 5-9% incidence of HER2/neu amplification in CRC 26,27 and HER2/neu amplification was shown to be concordant in only 5% of the primary and metastatic lesions. 27 In a study by Ramanathan et al, HER2/neu-positive patients with advanced colorectal cancer were treated with trastuzumab (Herceptin Ò and irinotecan). Of the 138 screened patients, Her2 protein overexpression was only detected in 11 (8%; 2+ in 5 and 3+ in 6 patients), and this resulted in premature termination of the study.…”
Section: Discussionmentioning
confidence: 86%
“…Previous studies have reported ERBB2 and EGFR amplifications to occur in 0% to 25% and 1% to 8% of colorectal carcinoma patients (911); with a degree of heterogeneity (15% of cases) between amplification status in different lesions (10). Our results are concordant with both general incidence in colorectal carcinoma patients and heterogeneity; however, our heterogeneity was intratumoral and demonstrated by percent of tumor cells staining with IHC.…”
Section: Discussionmentioning
confidence: 99%
“…4 Methodologies for HER2 testing and defining positivity in mCRC are not yet standardized, and efforts to standardize testing in order to identify patients who may be eligible for HER2-directed treatment are underway. 68 …”
Section: Discussionmentioning
confidence: 99%
“…1214 Notably, approximately 15% discordance between HER2 expression in colon primaries and metastases has been reported, and HER2 expression may change over time, highlighting the need to further prospectively study the role of HER2 in mCRC. 6 The prognostic effect of HER2 overexpression in mCRC remains unclear, with conflicting evidence from retrospective analyses. 8,14 Another factor yet to be explored in CRC is the interplay of MYC alterations with HER2 overexpression.…”
Section: Discussionmentioning
confidence: 99%